2020
DOI: 10.3233/bpl-190090
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor-MRI detects exercise-induced neuroplasticity in the hippocampal microstructure in mice

Abstract: Background: Despite considerable research on exercise-induced neuroplasticity in the brain, a major ongoing challenge in translating findings from animal studies to humans is that clinical and preclinical settings employ very different techniques. Objective: Here we aim to bridge this divide by using diffusion tensor imaging MRI (DTI), an advanced imaging technique commonly applied in human studies, in a longitudinal exercise study with mice. Methods: Wild-type mice were exercised using voluntary free-wheel ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…In contrast, no impact of exercise could be detected in ROI located in GM. Previous research has shown that aerobic excise positively correlates with FA values measured with DTI in healthy individuals/animals ( Johnson et al, 2012 ; Chaddock-Heyman et al, 2018 ; Islam et al, 2020 ). Our study is the first DTI study that recapitulates the positive effects of voluntary exercise on WM fiber integrity in stroke induced mice.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, no impact of exercise could be detected in ROI located in GM. Previous research has shown that aerobic excise positively correlates with FA values measured with DTI in healthy individuals/animals ( Johnson et al, 2012 ; Chaddock-Heyman et al, 2018 ; Islam et al, 2020 ). Our study is the first DTI study that recapitulates the positive effects of voluntary exercise on WM fiber integrity in stroke induced mice.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, just as it happens with learning, depending on the frequency of stimulation (or repetition of conduct), these initial dynamic neuro-plastic adaptations can develop into more stable structural adaptations (i.e., WM integrity above). In other words, the initial neuroplastic changes at the functional level might foment longer-term protective adaptations that can persist for months or years ( Islam et al, 2020 ; Wilde et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, mice with access to a running wheel exhibit a significant increase in hippocampal neurogenesis and enhanced spatial and temporal memory [ 27 ]. Magnetic resonance imaging (MRI) studies revealed that extended voluntary exercise increases hippocampal volume in mice [ 28 ]. Similar findings were also reported in human studies.…”
Section: Exercise-induced Factors and Neural Plasticitymentioning
confidence: 99%